Kassandra: A framework for distributed simulation of heterogeneous cooperating objects - Mulero, M. (2016)
To address the heterogeneity and scalability issues of simulating Cooperating Objects (COs) systems, we propose . Kassandra, a conceptual framework for enabling distributed COs simulation by integrating existing simulation tools. Moreover, . Kassandra exploits the communication middleware used by real-world COs as underlying communication mechanism for integrating . Kassandra-enabled simulation tools. In this way, real-world COs can be included with simulated objects in a seamless way to perform more accurate system performance evaluation. Moreover, such a hardware-in-the-loop approach is not limited to pre-deployment performance analysis, and can offer possibilities to analyse performance at different phases of CO applications. The concept of . Kassandra has been carried out in the EU PLANET project. In this paper, we introduce the . Kassandra framework components and show their interactions at different phases for node deployments in PLANET use cases. The result demonstrates the applicability of . Kassandra to facilitate the development of CO applications. © 2016 Elsevier B.V.